A Study of sensory and nutritional quality of virgin olive oil. Presentation of a European project of research - Giovanni Esposito; Claudio Peri (Grasas y Aceites)
The purpose of this paper is to present, in a synthesis, the objectives and means of the FLAIR project on olive oil quality (FLAIR proposal N.- 89041, contract N° AGRF - GT91 - 0046). Comments are reported on the scientific assumptions and practical problems that have motivated this research. The participants are also presented with their roles and tasks in the project.